Return to Preinjury Status after Routine Knee Arthroscopy in Military Population - Joshi, A; Kayastha, N; Maharjan, R; Chand, P; KC, B R (Journal of Nepal Health Research Council, 2014)
Background: Knee arthroscopy is frequently advised procedure for knee-related problems in serving soldiers. The scanty published literatures have documented wide range of recovery duration ranging from nine days to four weeks even for routine uncomplicated arthroscopy. However, neither of these studies evaluated military population, where arthroscopic procedures are frequent and physical demands are different. The aim of this study was to ascertain the time required to return to unrestricted physical activities in serving military population.Methods: This was a prospective descriptive study enrolling 51 patients who underwent two portal arthroscopic procedures like diagnostic arthroscopy, meniscectomy, loose body removal and excision of plica or combination of these. A uniform home based physiotherapy protocol was used for everyone. All of them were followed up at 2nd, 4th, 6th, 8th and 12th postoperative weeks. At each follow up, 2000 International Knee Documentation Committee subjective knee evaluation form was filled and submitted for analysis. Results: Although all of our patients were able to walk around without any support at two weeks follow up, 88% had restriction to activities of daily living because of knee related problems. The mean International Knee Documentation Committee score was 41 at 1st follow up, which gradually improved to 64, 86, 94, 94 at 4 week follow up respectively. At 6 weeks 91% resumed their preinjury status which reached 94% in eight weeks.Conclusions: Most of the soldiers return to unrestricted activities within six to eight weeks after diagnostic arthroscopy, meniscectomy, loose body removal and excision of plica or combination of these procedures. Keywords: arthroscopy; military; pysical activity.